People versus Machines: The Impact of Being in an Automatable Job on Australian Worker's Mental Health and Life Satisfaction - Grace Lordan; Eliza-Jane Stringer (Institute of Labor Economics (IZA), 2022)
This study explores the effect on mental health and life satisfaction of working in an automatable job. We utilise an Australian panel dataset (HILDA), and estimate models that include individual fixed effects, to estimate the association between automatable work and proxies of wellbeing. Overall, we find evidence that automatable work has a small, detrimental impact on the mental health and life satisfaction of workers within some industries, particularly those with higher levels of job automation risk, such as manufacturing. Furthermore, we find no strong trends to suggest that any particular demographic group is disproportionately impacted across industries. These findings are robust to a variety of specifications. We also find evidence of adaptation to these effects after one-year tenure on the job, indicating a limited role for firm policy.
Keywords: I10; J20; 330; automation; life satisfaction; mental health; job security